2000
DOI: 10.1093/clinchem/46.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Clinical Performance of a Detergent-based Homogeneous LDL-Cholesterol Assay: A Multicenter Evaluation

Abstract: Background: LDL-cholesterol (LDL-C) concentrations currently are determined in most clinical laboratories using the Friedewald calculation. This approach has several limitations and may not always meet the current total error recommendation in LDL-C measurement of ≤12% established by the National Cholesterol Education Program. Methods: In a multicenter study, we evaluated the analytical and clinical performance of a homogeneous LDL-C assay (LDL-CRoche; Roche Diagnostics, Indianapolis, IN) in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…Strategies for treatment of lipid abnormalities are primarily based on LDL-C concentration. Therefore, LDL-C must be [8,11]. Some authors have demonstrated that the formula should not be used in certain groups of patients with diabetes, liver and renal dysfunction even with TG levels \4.52 mmol/l [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Strategies for treatment of lipid abnormalities are primarily based on LDL-C concentration. Therefore, LDL-C must be [8,11]. Some authors have demonstrated that the formula should not be used in certain groups of patients with diabetes, liver and renal dysfunction even with TG levels \4.52 mmol/l [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the presence of small amounts of chylomicrons or abnormal lipoproteins, the formula gives rise to falsely low LDL cholesterol values. As well, the homogenous Roche method we have used has some limitations [6] although it has been reviewed by Nauck et al [11] to be precise and acceptably accurate. It gives an improvement in the measurement of LDL-C in samples with high TG and may assist better in classification of patients at risk categories for cardiovascular diseases than Friedewald's equation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations